Pembuatan Rumah Pangan Lestari Sebagai Upaya Mempertahankan Status Zero Stunting Di Kampung Tanoh Depet - Yulida Fitri; Rahmadhansyah Rahmadhansyah; Nurkamalia Nurkamalia; Nur Isnaini; Ibnu Hajar Aswat; Sofiyanurrianti Sofiyanurrianti (Universitas Maritim AMNI Semarang, 2023)
Tanoh Depet Village isoneof the villages in the Celala District, Central Aceh District. Tanoh Depet Village is located in an area that is remote in the Celala District with vast natural potential with agriculturall and plantations. Base dont here sult sof a survey conducted, the total population in Tanoh Depet Villageis 169 Family Cards. Tanoh Depet Village currently holds Zero Stunting status, but the local community isstill very lacking in education about how tomaintain Zero Stunting status, there fore the presen ceof Regular KKN students in the village creates a program, namely Sustainable Food Homes as an effort tomaintain Zero Stunting status in Tanoh Depet Village. The implementation of the construction of Sustainable Food Home supto the socializations tageto the community consists of several stages which include: (1) Land clearing (2) Preparation of see dsand planting of herb sand vegetables (3) Making of bars for sustainable food houses (4) Socialization of Sustainable Food Homes to community (5) Question and answer session.